14. CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS WITH ACUTE PANCREATITIS DUE TO HYPERTRIGLYCERIDEMIA (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics of patients diagnosed with acute pancreatitis due to hypertriglyceridemia.Subjects and Methods: A cross-sectional descriptive study was conducted on 71 patients diagnosed with hypertriglyceridemia-induced acute pancreatitis from January 2023 to December 2024.Results: Among the 71 patients, the mean age was 42.5 ± 10.2 years, and 67.6% were male. Common symptoms included abdominal pain (100%), nausea/vomiting (91.5%), and abdominal distension (87.3%). The mean serum triglyceride level was 1200 ± 650 mg/dL, and the mean blood glucose level was 150 ± 45 mg/dL. The proportions of patients with mild, moderate, and severe pancreatitis were 39.4%, 35.2%, and 25.4%, respectively. Severe cases were associated with higher triglyceride and glucose levels as well as delayed hospital admission (p < 0.05).Conclusion: Acute pancreatitis due to hypertriglyceridemia commonly affects middle-aged men, with disease severity associated with metabolic disturbances and delayed hospital presentation.
Keywords: Acute pancreatitis; hypertriglyceridemia; metabolic disturbances